Evaluating protective helmet efficacy in work-related accident: A forensic biomechanical analysis of concussion risk from falling objects - Horak, Zdenek; Tichy, Petr; Vilimek, Miloslav (Legal medicine, 2024)
This study investigates the risk of head injuries, specifically concussions, from falling objects in workplace accidents. A case study focuses on a construction worker who sustained a head injury despite wearing a protective helmet. Utilizing finite element (FE) analysis, the helmet-head system was modeled to assess impact forces and head accelerations. The helmet, made of High-Density Polyethylene with a 6-point suspension system, was tested against falling objects of 332 g and 665 g. Simulations, conducted from heights of 5 to 25 m, revealed that objects weighing as little as 332 g could cause severe concussions from a 10-meter fall. These findings demonstrate that helmets, while mitigating some impact, absorb significantly less energy than the kinetic energy of falling objects. The analyses carried out confirmed the worker's statement that his injury was caused by a foreign object falling on his head, which was protected by a helmet.
Keywords: Accidental Falls; komoce mozku; Accidents, Occupational; pracovní nehody; Finite Element Analysis; analýza metodou konečných prvků; biomechanika; lidé; Brain Concussion; prostředky k ochraně hlavy; úrazy pádem; Head Protective Devices; Biomechanical Phenomena; Humans